Optimal combinations of PV, wind, micro-hydro and diesel systems for a seasonal load demand - Khan M.R.B.; Jidin R.; Pasupuleti J.; Shaaya S.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper proposes multiple optimal combinations of hybrid renewable energy systems for a resort island based on actual generation-side energy auditing, assessment of seasonal renewable energy resources availability versus load profiles, and techno-economic analyses. Tioman Island is selected for this study as it represents the typical energy demands of many resort islands in the South China Sea. The island depends primarily on diesel-fuel for electricity generation. As a result, the generating company is exposed to diesel fuel volatile market prices and high operation and maintenance costs. Moreover, the diesel power plant poses possible risk of fuel spills and environmental degradation. Hence, to mitigate the diesel fuel dependence, an optimal combination of hybrid diesel and renewable energy is proposed. The study starts with an actual generation-side auditing, which includes distribution of loads, seasonal load profiles, and types of loads as well as an analysis of local development planning. Subsequently, surveys of available renewable resource potentials such as solar, wind, and hydro have been conducted that involved collection and analysis of meteorological data. Finally, HOMER software was used to perform techno-economic analyses for different combinations of hybrid energy system. Results of the analyses include the optimal hybrid system configurations, cost of the hybrid system, fuel saving, and CO2 emission reduction. © 2014 IEEE.